Social and labour rights in a global context : (Cambridge University Press, 2002)
Essays by leading scholars from the U.K., Ireland, France, Germany, Italy, Japan and the U.S. question the effectiveness of the new rhetoric of rights, the contributors examine emerging new approaches at the international, multinational companies